2009
DOI: 10.1016/j.jpainsymman.2009.02.230
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Induced Respiratory Depression Resulting from Transdermal Fentanyl-Clarithromycin Drug Interaction in a Patient with Advanced COPD

Abstract: Levomepromazine, also known as methotrimeprazine, is an antipsychotic drug. In addition to this use, it has a role in palliative care for the alleviation of nausea. It also has been used to manage terminal restlessness, although it can cause restlessness and akathisia.Drug-induced lupus is a condition that resembles a mild form of idiopathic systemic lupus erythematosus and is associated with drugs such as procainamide, hydralazine, minocycline, quinidine, chlorpromazine, isoniazide, and methyldopa. 1,2 It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Opioids are the most powerful analgesics with side effects such as the risk of ventilatory depression and apnea (12,14,44,52). The latter could be lethal (16,44), especially in some patients with pulmonary diseases such as chronic obstructive pulmonary disease (4,15,18). Many studies have shown that pulmonary inflammatory mediators-hypoxemia and hypercapnia, congestion, and edema-that are common in patients with these diseases, can sensitize and/or stimulate PCFs to prolong PCFmediated apnea (8,17,41).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Opioids are the most powerful analgesics with side effects such as the risk of ventilatory depression and apnea (12,14,44,52). The latter could be lethal (16,44), especially in some patients with pulmonary diseases such as chronic obstructive pulmonary disease (4,15,18). Many studies have shown that pulmonary inflammatory mediators-hypoxemia and hypercapnia, congestion, and edema-that are common in patients with these diseases, can sensitize and/or stimulate PCFs to prolong PCFmediated apnea (8,17,41).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Fatal drug interactions between fentanyl and CYP3A inhibitors, eg, fluconazole, clarithromycin, diltiazem, and itraconazole have been reported in chronic pain patients treated with transdermal fentanyl resulting in opioid intoxications of these patients …”
mentioning
confidence: 99%
“…RSB commonly occurs in patients with pulmonary inflammation (infection), congestion, and edema (Churchill & Cope, 1929; Hatridge et al , 1989; Roussos & Koutsoukou, 2003). These patients are more vulnerable to suffering from respiratory depression and even respiratory failure than normal subjects when opioids are administered as analgesics, mainly due to acting on μ-receptors, in the clinical setting (Gruber & Tschernko, 2003; Horton & Barber, 2009). However, the reason for this vulnerability is not clear.…”
Section: Discussionmentioning
confidence: 99%